Use of Three-Dimensional Basement Membrane Cultures to Model Oncogene-Induced Changes in Mammary Epithelial Morphogenesis - Mills Shaw, Kenna R. (2004)
The development of breast carcinomas involves a complex set of phenotypic alterations in breast epithelial cells and the surrounding microenvironment. While traditional transformation assays provide models for investigating certain aspects of the cellular processes associated with tumor initiation and progression, they do not model alterations in tissue architecture that are critically involved in tumor development. In this review, we provide examples of how three-dimensional (3D) cell culture models can be utilized to dissect the pathways involved in the development of mammary epithelial structures and to elucidate the mechanisms responsible for oncogene-induced phenotypic alterations in epithelial behavior and architecture. Many normal mammary epithelial cell lines undergo a stereotypic morphogenetic process when grown in the presence of exogenous matrix proteins. This 3D morphogenesis culminates in the formation of well-organized, polarized spheroids, and/or tubules that are highly reminiscent of normal glandular architecture. In contrast, transformed cell lines isolated from mammary tumors exhibit significant deviations from normal epithelial behavior in 3D culture. We describe the use of 3D models as a method for both reconstructing and deconstructing the cell biological and biochemical events involved in mammary neoplasia.